ANALISIS PEMBUBARAN PARTAI POLITIK OLEH MAHKAMAH KONSTITUSI - Hidayat, Bagaskara Rahmat; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2024)
Since this authority was given to the constitutional court, the Constitutional Court itself has never tried a case regarding the dissolution of a political party. Seeing this situation, there is an assumption that authority is useless, which is considered reasonable considering the cases of KKN that mostly happen to a political party, but because of the pretext that the "ideology" of political parties is in line with Pancasila, it is not followed up. Another problem also arises in the Act on the procedure for dissolving political parties which specializes only certain people who can become applicants, namely the government, the urgency to overcome this problem can be seen that it is the support of political parties that makes most of the "government" categories able to occupy their positions. The approach method used in this study is a normative juridical approach, because the problem to be studied has to do with the authority of the Constitutional Court and the philosophical, juridical, and sociological basis of the position and authority of the Constitutional Court in the dissolution of political parties in Indonesia. From a juridical perspective, of course, it is explained how the procedure for the dissolution of a political party is explained, in practice it cannot be said to be in line, nor can it be said otherwise, given that this authority has not been used. Another perspective also looks at the reasons the constitutional court has not tried cases related to the dissolution of political parties.